"[It] Changed Everything": The Effect of Shifting Social Structures on Queer L2 Learners' Identity Management. Issue 3 (4th May 2023) - Moore, Ashley R.
ABSTRACT: Despite a growing body of knowledge regarding the relevance of queer people and their lives to language education, we still know little about the power of classrooms, institutions, and larger macro structural forces to shape—and be shaped by—the identity experiences of queer L2 learners. This article presents a comparative analysis of the identity dilemmas and decisions of two queer learners as they studied Japanese in their home countries (the United States and Romania) and Japan. The findings show that the participants had learned to view their queer identities as incompatible with the compulsory cisgenders and heterosexuality reproduced in the social setting of the L2 classroom. My analysis underscores the crucial role that institutional policies and practices have on the well-being of queer students. The comparative analysis also highlights the objective/subjective duality of macro social structures and how they come to mean in the lives of learners.